Life Events, Coping, and Posttraumatic Stress Symptoms among Chinese Adolescents Exposed to 2008 Wenchuan Earthquake, China - Zheng, Yuhong; Fan, Fang; Liu, Xianchen; Mo, Lei (PLOS ONE, 2012)
Purpose To examine the relationship between negative life events, coping styles, and symptoms of post-traumatic stress disorder (PTSD) among adolescent survivors exposed to 2008 Wenchuan Earthquake, China. Methods A survey was conducted in a sample of 2250 adolescent students from two schools in Dujiangyan District, a seriously damaged area, 20 kilometers away from the epicenter, 6 months after the earthquake. Participants completed a self-administered questionnaire including demographics, negative life events, coping styles, and PTSD symptoms. Results Academic pressure was the strongest predictor of adolescents' PTSD symptoms among all negative life events. Main effects of negative life events, positive coping and negative coping on PTSD symptoms were significant in both younger adolescents and older adolescents, while the moderator effects of two coping styles were found significant only within older adolescents. Conclusions Coping may play a role to moderate the relationship between post-earthquake negative life events and PTSD symptom, but the function seems to depend on the age of participants. Psychosocial coping skills training may be important in the prevention and intervention of mental health problems in adolescent survivors of traumatic earthquake.